(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS: Is the novel in-vitro diagnostic device U-Test® reliable and secure for urine collection in diaper-wearing children and simultaneous evaluation of the urine collected for the presence of leucocytes and nitrite? METHODS: The qualitative and functional performance of U-Test® was evaluated in a multicentre prospective clinical trial. The diagnostic performance of the novel in-vitro diagnostic device was determined in reference to the established procedure involving urine sampling by urine-bag, clean-catch, catheterisation and suprapubic aspiration followed by dipstick analysis and urine culture, and in an in-vitro study. RESULTS: U-Test® proved to be comfortable and secure for the child and well accepted by the persons responsible for the participating children. No undesired side-effects were seen and in 75.8% (95% CI ± 10.5%; n = 66) of the tests used, enough urine was collected within the permitted time for immediate and successful urine analysis by the integrated test card. Diagnostic performance was found to be comparable to the established procedure using dipstick analysis (leucocytes: κ-coefficient 0.86; nitrite: κ-coefficient 0.74; n = 150). Sensitivity of the U-Test® for leucocyte detection was found to be 96.7% and specificity 100.0%. For nitrite detection sensitivity of 90.0% and specificity of 98.3% were found. CONCLUSIONS: The evaluation shows that U-Test® is a safe and reliable device of high functionality and diagnostic performance for the detection of leucocytes and nitrite directly and without time delay in a child’s diaper. This statement is based on a comprehensive comparison of the novel device with accepted diagnostic test systems and procedures based on the same dry chemistry technology. Due to its simplicity of use, U-Test® can be considered an alternative to the cumbersome procedures of urine collection by the bag-method or clean-catch followed by dipstick analysis for the presence of leucocytes and nitrite.